The Potential Development of Android-Based Lesson Study in Mathematics Learning at Junior High Schools - Anita Dewi Utami; Rofiki, Imam; Suwarman, Ramdhan Fazrianto; Listiawan, Tomi; Manunggal, Deddy Trisna; Dyaswardani, Hapsari; Akmalia, Yuyun (Jurnal Pendidikan Edutama, 2025)
Mathematics learning in junior high schools often faces challenges such as low conceptual understanding and limited teacher collaboration. Android-based Lesson Study (LS) offers a promising solution through technology integration, but related research is still scarce. This study analyzes the potential of Android-based LS for mathematics learning in junior high schools based on Scopus-indexed literature. A systematic literature review (SLR) was conducted using the PRISMA protocol. Searches in Scopus used the keywords "Lesson Study," "Android app," "mathematics education," and "secondary school," filtered by: (1) 2019–2024 publications, (2) journal articles only, and (3) full-text availability. Of 78 articles identified, 15 met the inclusion criteria. Results show: (1) 80% highlight Android apps’ effectiveness in improving teacher collaboration; (2) 60% report enhanced student motivation via interactive media; (3) main challenges involve teachers’ TPACK and infrastructure. The study concludes Android-based LS has strong potential for junior high schools, especially with adequate TPACK training.